Tea consumption and attenuation of biological aging: a longitudinal analysis from two cohort studiesResearch in context - Yi Xiang; Hao Xu; Hongxiang Chen; Dan Tang; Zitong Huang; Yuan Zhang; Zhenghong Wang; Ziyun Wang; Yangla; Mingming Han; Jianzhong Yin; Xiong Xiao; et al. (Elsevier, 2024)
Summary: Background: The biological aging process can be modified through lifestyle interventions to prevent age-related diseases and extend healthspan. However, evidence from population-based studies on whether tea consumption could delay the biological aging process in humans remains limited. Methods: This study included 7931 participants aged 30-79 years from the China Multi-Ethnic Cohort (CMEC) Study and 5998 participants aged 37-73 years from the UK Biobank (UKB) who participated in both the baseline and first follow-up surveys. Tea consumption information was collected through questionnaires. Biological age (BA) acceleration was calculated using clinical biomarkers and anthropometric measurements based on the Klemera Doubal method (KDM). Change-to-change analyses were performed to estimate the associations between changes in tea consumption status and changes in BA acceleration using multiple linear models. Follow-up adjusted for baseline analyses were further conducted to examine the prospective exposure-response relationship between tea consumption and BA acceleration among individuals with constant tea consumption status. Findings: During a median follow-up of 1.98 (1.78, 2.16) years in the CMEC and 4.50 (3.92, 5.00) years in the UKB, tea consumption was consistently associated with attenuated BA acceleration in both cohorts. Transitioning from nondrinking to tea-drinking was associated with decreased BA acceleration (CMEC: β = −0.319, 95% CI: −0.620 to −0.017 years; UKB: β = −0.267, 95% CI: −0.831 to 0.297 years) compared to consistent nondrinking. Even stronger associations were found in consistent tea drinkers. The exposure-response relationship suggested that consuming around 3 cups of tea or 6-8 g of tea leaves per day may offer the most evident anti-aging benefits. Interpretation: Tea consumption was associated with attenuated BA acceleration measured by KDM, especially for consistent tea drinkers with moderate consumption. Our findings highlight the potential role of tea in developing nutrition-oriented anti-aging interventions and guiding healthy aging policies. Funding: National Natural Science Foundation of China (Grant No. 82273740).